Margins of multinational labor substitution - Marc-Andreas Muendler; Sascha O. Becker (Institute for the Study of Labor (IZA), 2006)
Multinational labor demand responds to wage differentials at the extensive margin, when a multinational enterprise (MNE) expands into foreign locations, and at the intensive margin, when an MNE operates existing affiliates across locations. We derive conditions for parametric and nonparametric identification of an MNE model to infer elasticities of labor substitution at both margins, controlling for location selectivity. Prior studies have rarely found foreign wages or operations to affect employment. Our strategy detects salient adjustments at the extensive margin for German MNEs. With every percentage increase in German wages, German MNEs allocate 2,000 manufacturing jobs to Eastern Europe at the extensive margin and 4,000 jobs overall.
Keywords: F21; F23; C14; C24; J23; 330; multinational enterprise; location choice; sample selectivity; labor demand; translog cost function; nonparametric estimation; Multinationales Unternehmen; Betriebliche Standortwahl; Arbeitsnachfrage; Substitutionselastizität; Deutschland